Adopsi Sebagai Upaya Melindungi Hak-Hak Anak Dalam Perspektif Hukum Islam - Karimatul Ummah (Fakultas Hukum Universitas Islam Indonesia, 2005)
Adoption is intended to protect the rights of the children toward their future. However, adoption does not automatically change the legal status of the adopted child to be someone's own flesh and blood. The legal status of adopted child to have the right of inheritance depends on what kinds of legal systems used to resolve the inheritance. In Islamic Law Compilation adopted child is not the heir, but he has a right to obtain the will (wasiatwajibah).